Pengaruh Strategi Pembelajaran DAP (Developmentaly Appropriate Partice) Terhadap Kemampuan Kognitif Siswa Pada Mata Pelajaran Fiqih Kelas VII MTs Madinatul Ilmi Lubuk Kertang Kecamatan Berandan Barat - Novia Sri Rahayu, Muhammad Saleh, Nurmisda Ramayani (Pusdikra Publishing, 2023)
Internal problemsthe learning process of students is less motivated to learn, because the strategies applied in learning are still monotonous, so that students are less interested in following the material presented by the teacher. For this in motivating students in teaching and learning activities, the authors try to apply the Developmentally Appropriate Practice (DAP) learning strategy..This study uses a type of quantitative research. The results of this study indicated thatThe results of calculations using simple regression analysis show a significant value from the coefficient table obtained a significance value of 0.000 <0.05 and based on the T test it is known that the value of tcount is 20,662 > ttable 1,677. Through this analysis it can be concluded that the DAP strategy (Developmentally Appropriate Partice) influences the results Cognitive students in Class VII Jurisprudence subjects at MTs Madinatul Ilmi Lubuk Kertang, Brandan Barat District. The influence of the DAP (Developmentaly Appropriate Partice) strategy applied to Jurisprudence subjects can be said to be effective, this can be seen from the answers to the class VII student questionnaire with a total of 51 students, the answer has a percentage result of 100%.